Isolation and Molecular Characterization of Vancomycin‐Resistant Enterococcus faecium from Swine in Michigan, USA. (7th September 2012) - Gordoncillo, M. J. N.; Donabedian, S.; Bartlett, P. C.; Perri, M.; Zervos, M.; Kirkwood, R.; Febvay, C.
Summary In 2008, we identified vancomycin‐resistant enterococci (VRE) in Michigan swine, which was the first report of VRE in livestock from North America. Continued sampling in 2009 and 2010 was conducted to determine whether VRE persisted in Michigan. In 2009, swine faecal and feed samples (n = 56), county fair pig barn manure samples (n = 9) and pooled Michigan State Fair pig barn manure samples (n = 18) were screened for VRE. In 2010, swine faecal samples were collected from 26 county fairs (n = 73) and nine commercial swine farms in six states (n = 28). Recovered VRE isolates were molecularly evaluated by polymerase chain reaction, restriction fragment length polymorphism, pulsed‐field gel electrophoresis (PFGE), S1 nuclease digestion and multilocus sequence typing (MLST). Six VRE isolates were identified in 2009 from the State Fair, and another six (8.2%) were recovered from the five county fairs in 2010. All 12 isolates were highly related to the first‐reported VRE from Michigan swine: all were confirmed to be vancomycin‐resistant Enterococcus faecium (VREf) carrying vanA gene on Tn1546 (Type D), were negative for IS1251, hyl and esp gene, carried a 150–160 kb megaplasmid, and have closely similar PFGE patterns with >80% similarity. Classified as ST5, ST6 or ST185 by MLST, all belong to the clonal complex 5, a strain recognized to be circulating among European pigs. This study reveals that VREf are widespread in Michigan swine and persist in the historical absence of the use of agricultural glycopeptides.